John William Jagger and the South African railways, 1921-1924 - Bissett, James (Department of Historical Studies, 2016)
The Major problems facing me during both the research and the writing of this essay were the material available and the nature of the subject. Initially, both the necessary material and Jagger's character and role as Minister of Railways seemed remarkably elusive. The nature of the material available tended to enforce a reliance on Jagger's actions in parliament and the crises which he faced on that somewhat isolated stage, and on the gleanings from an almost exclusively partisan press. Jagger himself was a humourless, dry and lonely man whose private life remained his own business. His public career was the common story of the "boy with brains" who "did well in the Colonies". Another problem arises out of the fact that Jagger was appointed Minister of Railways and Harbours, a portfolio as dry as his personality. These factors go a long way towards explaining the generally uncontroversial nature of the material presented in this essay. Any dullness and related deficiencies are, of course, entirely the fault of the writer. It could be asked of what possible significance grain elevators, harbour extensions and railway deficits are. It is unlikely that any of these features will ever be considered to be of major significance to the history of South Africa in the twentieth century. In fact it could never really be said that J.W.Jagger was of major significance to South African history. What is presented here, however, be it dry statistics or seemingly absurd scandals about grain elevators or harbour extensions, is what Jagger himself found compelling. These aspects of South African life, the economic aspects, are where Jagger found fulfilment. To many this may seem incomprehensible, but this was Jagger's life. Life, after all, is at the core of history and it is only by immersing ourselves in the past, as historians, that we can hope to understand the present. Thus Jagger's life - albeit a dry and humourless life - is history; it lives; it is the "stuff of which dreams are made". Statistics and ways and means of economising comprise the essence of both Jagger's term of office as Minister of Railways and Harbours, and in fact of his entire life. The making of money, the best ways of saving it, and the best ways of spending it for the good of the nation comprise the essence of his career.